Optimization of highly efficient exogenous-DNA-free Cas9-ribonucleoprotein mediated gene editing in disease susceptibility loci in wheat (Triticum aestivum L.) - Poddar, Snigdha; Tanaka, Jaclyn; Running, Katherine L. D.; Kariyawasam, Gayan K.; Faris, Justin D.; Friesen, Timothy L.; Cho, Myeong-Je; Cate, Jamie H. D.; Staskawicz, Brian (Frontiers in Plant Science, 2023)
The advancement of precision engineering for crop trait improvement is important in the face of rapid population growth, climate change, and disease. To this end, targeted double-stranded break technology using RNA-guided Cas9 has been adopted widely for genome editing in plants. Agrobacterium or particle bombardment-based delivery of plasmids encoding Cas9 and guide RNA (gRNA) is common, but requires optimization of expression and often results in random integration of plasmid DNA into the plant genome. Recent advances have described gene editing by the delivery of Cas9 and gRNA as pre-assembled ribonucleoproteins (RNPs) into various plant tissues, but with moderate efficiency in resulting regenerated plants. In this report we describe significant improvements to Cas9-RNP mediated gene editing in wheat. We demonstrate that Cas9-RNP assays in protoplasts are a fast and effective tool for rational selection of optimal gRNAs for gene editing in regenerable immature embryos (IEs), and that high temperature treatment enhances gene editing rates in both tissue types. We also show that Cas9-mediated editing persists for at least 14 days in gold particle bombarded wheat IEs. The regenerated edited wheat plants in this work are recovered at high rates in the absence of exogenous DNA and selection. With this method, we produce knockouts of a set of three homoeologous genes and two pathogenic effector susceptibility genes, engineering insensitivity to corresponding necrotrophic effectors produced by Parastagonospora nodorum. The establishment of highly efficient, exogenous DNA-free gene editing technology holds promise for accelerated trait diversity production in an expansive array of crops.